لغة لورنس العربية في كتاب "أعمدة الحكمة السبعة" وردها إلى أصلها العربي: عرض وتحليل (Advocacy of Lawrence' Arabic Language in his Book "Seven Pillars of Wisdom") - (Mustafa Soleh al-Said), مصطفى صالح السعيد (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: تُرجم كتاب توماس إدوارد لورنس "أعمدة الحكمة السبعة"، من الإنجليزية؛ حيث يسرد فيه ذكرياته. والمتصفح للترجمات وبعض المصادر التي تتحدث عن الثورة العربية الكبرى، أو حياة لورنس ودوره في تلك الثورة يجد عاملاً مشتركاً بينه وهو وجود أسماء أماكن وأشخاص بعيدة لا تتطابق مع الأصل العربي كما سنرى لاحقاً، ومثل هذه الترجمات والمصادر تربك الباحث الذي يريد معلومات عن الأشخاص والأماكن، فهي لا تقدم له أسماء صحيحة، ونتيجة لذلك تكون المعلومات التي يقدمها في بحثه غير دقيقة لاعتماده على مثل هذه المصادر؛ ولذلك تتناول هذه الدراسة لغة لورنس العربية وما أورده في كتاب "أعمدة الحكمة السبعة" من عبارات عربية مترجمة حرفيا إلى الإنجليزية، وأسماء العلم من أماكن وأشخاص مبيّنة كيف أعيدت إلى أصلها العربي من اللغة الإنجليزية، وتكشف عن العلل الكامنة وراء الأخطاء في رد هذه الأسماء إلى أصلها العربي. الكلمات المفتاحية: أعمدة الحكم- لغة لورنس- نماذج- الترجمة- الأخطاء. Abstract: Thomas Edward Lawrence’s book “Seven Wisdom Pillars” was translated from English language, where he narrated his memory. Whoever handle the translated and some references that discussed largest Arab revolution, or life of Lawrence and his role in that revolution, will see some similarities between them. Starting from name of some places and personalities which are so far, and do not correspondent with the Arabic original as we shall see it sooner. This type of translation and references will confused the researcher who is searching for information about people or places. It doesn’t produce for him correct names. Consequently, the information been mentioned in his work will be not be detailed for been depended on these references. For this reason, this paper is going to study Lawrence Arabic language, and what he mentioned in the book “Seven Wisdom Pillars” from Arabic statements which was translated to English Language literally, such as some personal names, places and people. It will explain how to change them to their Arabic origin from English Language. The study will expose the reasons for those mistakes in returning these names to their Arabic origins. Keywords: Wisdom Pillars- Lawrence language- Sample- Translation- Mistakes. Abstrak: Buku karangan Lawrence of Arabia yang berjudul “ The Seven Pillars of Wisdom” telah diterjemahkan ke dalam bahasa Arab. Ia memuatkan memoir tokoh tersebut. Terdapat beberapa nama-nama tempat dan individu dalam terjemahan tersebut yang tersasar daripada yang asalnya. Ini menyulitkan pengkaji yang inginkan maklumat tentang individu-individu dan tempat yang berkenaan kerana kesalahan tersebut. Kajian ini akan membentangkan bahasa yang digunakan oleh Lawrence of Arabia di dalam karangan beliau “ The Seven Pillars of Wisdom” yang mengandungi frasa-frasa Arab yang diterjemahkan secara literal ke dalam bahasa Inggeris termasuk nama-nama khas untuk individu dan tempat. Senarai ini kemudiannya akan dianalisa dan dikembalikan kepada bentuk Arabnya yang asal daripada bahasa Inggeris untuk memberikan sebab musabab berlakunya kesilapan tersebut. Kata kunci: Buku karangan- Bahasa Lawrence- Contoh- Terjemah- Kesilapan.